Verbal autopsy: current practices and challenges - Soleman Nadia; Chandramohan Daniel; Shibuya Kenji (The World Health Organization, 2006)
Cause-of-death data derived from verbal autopsy (VA) are increasingly used for health planning, priority setting, monitoring and evaluation in countries with incomplete or no vital registration systems. In some regions of the world it is the only method available to obtain estimates on the distribution of causes of death. Currently, the VA method is routinely used at over 35 sites, mainly in Africa and Asia. In this paper, we present an overview of the VA process and the results of a review of VA tools and operating procedures used at demographic surveillance sites and sample vital registration systems. We asked for information from 36 field sites about field-operating procedures and reviewed 18 verbal autopsy questionnaires and 10 cause-of-death lists used in 13 countries. The format and content of VA questionnaires, field-operating procedures, cause-of-death lists and the procedures to derive causes of death from VA process varied substantially among sites. We discuss the consequences of using varied methods and conclude that the VA tools and procedures must be standardized and reliable in order to make accurate national and international comparisons of VA data. We also highlight further steps needed in the development of a standard VA process.